The Hidden Paradise; Gap and culture shock in the transformation of a fishing villages into a tourism hotspots in Mandeh region, Indonesia - Fatimah, Siti; Syafrini, Delmira; Yuliana, Yuliana; Antomi, Yudi; Patra, Haldi; Mohamad Sharif, Sabri (Taylor & Francis Group, 2025)
The indigenous fishermen of the Mandeh region in Indonesia were living in seclusion, disconnected from the rest of the world before 2015. However, the captivating landscape of the region, featuring rolling hills, lush forests, thriving mangroves, and picturesque islets, remained hidden and unexplored. The region has experienced a substantial increase in tourism since 2015, prompting the government to establish it as the primary tourism hub. Therefore, this study aims to explore the transformation process of the Mandeh region from a fishing village into a tourism paradise. The historical method was used in this case, incorporating heuristic, criticism, analysis, and historiography stages. The documentation process involved the use of oral history techniques during the heuristic phase, with a total of 23 informants participating. Data collection was carried out through a productive Focus Group Discussion. The results showed a noticeable gap and culture shock experienced during the transition of a fishing village into a tourist destination. Future tourism policy should prioritise empowerment and hospitality programs, specifically in Mandeh integrated tourism area.